2016
DOI: 10.1002/etc.3552
|View full text |Cite
|
Sign up to set email alerts
|

Implications of fluoroquinolone contamination for the aquatic environment—A review

Abstract: Until recently, the behaviors of antibiotics and their ecotoxicological impact have been overlooked in the environment. The topic is broad and encompasses a wide range of organisms including microorganisms, algae, invertebrates, and vertebrates inhabiting various aquatic ecosystems. Changing the equilibrium of any 1 component in such systems disrupts the balance of the whole system. The manufacturing and frequent use of fluoroquinolones in human and animal medicine raises great concern over the increase of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(51 citation statements)
references
References 60 publications
1
45
0
Order By: Relevance
“…However, many people use the inadequate method for lack of choice (34). Several authors had demonstrated that environmental contamination is an important consequence provided by improper disposal of medicines (33,(40)(41)(42). The present data corroborate the literature since the studied population reported that inappropriate disposal might result in critical problems, as soil and water contamination.…”
Section: Resultssupporting
confidence: 89%
“…However, many people use the inadequate method for lack of choice (34). Several authors had demonstrated that environmental contamination is an important consequence provided by improper disposal of medicines (33,(40)(41)(42). The present data corroborate the literature since the studied population reported that inappropriate disposal might result in critical problems, as soil and water contamination.…”
Section: Resultssupporting
confidence: 89%
“…In recent years, antibiotics and fluoroquinolones have been widely used in the treatment of various infectious diseases due to their broad antibacterial spectrum and strong efficacy [1][2][3]. However, as the use of these antibiotics and fluoroquinolones increases, some of them have been detected in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…This antimicrobial class play a crucial role for the treatment of human and veterinary bacterial diseases. 3 Their slow rates of degradation and their persistence in the aquatic environment can increase the potential for formation of resistance mechanisms and ecotoxicity. 1,4,5 Moreover, sewage water treatment plants are not able to completely remove these compounds.…”
Section: Introductionmentioning
confidence: 99%